Rapid RP-HPLC technique for the determination of phyllanthin as bulk and its quantification in Phyllanthus amarus extract - Amene Alvari,; Mehrnaz S. Ohadi Rafsanjani,; Farhan J. Ahmed,; Mohd S. Hejazi,; Malik Z. Abdin, (International Journal of Phytomedicine, 2011)
A simple, specific and precise high performance liquid chromatographic method has been developed and validated for the estimation of Phyllanthin, an important bitter lignan present in Phyllanthus amarus. Furthermore, the developed method was used to successfully quantify the Phyllanthin in the plant extract also. The mobile phase optimized for the RP-HPLC was ethanol-water 66:34 (%v/v) and that was very simple and cost effective. The detection was carried out using variable wavelength UV–VIS detector set at 229 nm. Linearity for the developed method was found over the concentration range 1–50 μg/ml with a correlation coefficient of 0.999. Method was validated according to ICH guidelines and found to be suitable for rapid quantification of Phyllanthin in bulk and in plant extracts.